2019
DOI: 10.4102/hsag.v24i0.1284
|View full text |Cite
|
Sign up to set email alerts
|

Community service nurses’ experiences regarding their clinical competence

Abstract: Background: In South Africa, it is mandatory for nurses who have qualified as a nurse (general, psychiatric and community) and midwifery, leading to registration in Government Gazette Notice No. R425 of 22 February 1985, to perform 12 months’ compulsory community service after completion of training at a College of Nursing. Community service affords new graduate nurses the opportunity to improve their clinical skills and knowledge while nurturing professional behavioural patterns and critical thinking consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…The other concern raised by three experts is that the tool is evaluating clinical competence of CSNs in all disciplines, whereas some CSNs are not placed in those disciplines during their community service. This statement was supported by the results of objective 1 and 2 of this study, where some CSNs and PNs mentioned the challenges or discrepancies with CSNs’ allocations in the facilities (Matlhaba et al 2019 ). However, the researcher envisions that in the near future, specific CCETs can be developed where the focus will be on specific disciplines such as mental-health nursing and maternal and neonatal care.…”
Section: Research Purposesupporting
confidence: 76%
See 1 more Smart Citation
“…The other concern raised by three experts is that the tool is evaluating clinical competence of CSNs in all disciplines, whereas some CSNs are not placed in those disciplines during their community service. This statement was supported by the results of objective 1 and 2 of this study, where some CSNs and PNs mentioned the challenges or discrepancies with CSNs’ allocations in the facilities (Matlhaba et al 2019 ). However, the researcher envisions that in the near future, specific CCETs can be developed where the focus will be on specific disciplines such as mental-health nursing and maternal and neonatal care.…”
Section: Research Purposesupporting
confidence: 76%
“…It is noteworthy to mention that this research focuses predominantly on clinical competence of CSNs. Therefore, for the purpose of this research, clinical competence is considered the abilities of the CSNs to ‘work competently in providing quality nursing care to the patient under their care during community service period’ (Matlhaba, Pienaar & Sehularo 2019 ). For the 12-months community service period, CSNs are allocated in healthcare facilities such as clinics and hospitals and expected to perform delegated duties under the supervision of experienced professional nurses (Matlhaba et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This shortage of nurses has become a worldwide issue despite the vital role played by the nursing profession in the health care system ( Ubas-Sumagasyay & Oducado, 2020 ). In a study conducted in the North West Province, South Africa by Matlhaba, Pienaar and Sehularo (2019: 5) , it was determined that graduate nurses felt that they were ‘thrown into deep end and expected to swim’. Another study by Labrague et al (2019) of graduate nurses in the Philippines noted similar experiences, it was reported that these graduate nurses displayed significant levels of stress and disappointment due to the high expectations placed on them ( Labrague et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Health competency is the ability to accomplish something, in a specific situation, which is related to learning, knowledge acquisition and reconstructing knowledge. Thus, to develop effective health promotion actions, acquiring competencies is a guide for developing professional ability (10)(11) .…”
Section: Introductionmentioning
confidence: 99%